Pengetahuan Peternak Tentang Pemahaman Keterkaitan Gejala Birahi Dengan Keberhasilan Inseminasi Buatan Pada Sapi Di Kecamatan Samarinda Utara - Sava, Benediktus; Anindyasari, Dinar (CV. SINAR HOWUHOWU, 2026)
This descriptive-correlational study analyzes the knowledge of 33 cattle farmers in North Samarinda regarding AI and estrus symptoms. Using Spearman’s correlation and multiple linear regression ( = 55.1%), the results show that non-formal education significantly positive-impacts knowledge (β = 0.582; ρ < 0.001), while farming experience has a negative relationship (β = -0.493; ρ = 0.001). Position in farming is non-significant (ρ = 0.704). Although 55% of farmers possess very good knowledge, these findings highlight the necessity of continuous non-formal education to update modern reproductive technology skills, especially among experienced farmers.